Eksistensi Manusia dalam Perspektif Tasawuf - Lidinillah, Mustofa Anshori (Jurnal Filsafat "WISDOM", 2003)
There are two opiniors that are extremely different about tasawuf function in actualization human exsistence.Material object of the research is tasawuf concepts. Philosophical hermeneutic method used in this research. There are some procedures of method, namely, interpretation, analysis-synthesis, coherency,conparation, and heuristics.The results of the research are, according to tasawuf, there are two means of human exsistence. The first, as an exsistence, in the God-human relation context, the human as khalifatullah fil ard, the human are peace keeper in the world. Their action are actualization of God norms. The second, self consciousness as khalifatullah, its not principle diffrences; usually the one completes the orther. Tasawuf general orientation is to come to God, and become khalifatullah. Tasawuf can be an alternative procedure to human exsistence.